The burden of health expenditure on household impoverishment in Ethiopia: a systematic review and meta-analysis - Yawkal Tsega; Abel Endawkie; Shimels Derso Kebede; Natnael Kebede; Mengistu Mera Mihiretu; Ermias Bekele; Kokeb Ayele; Lakew Asmare; Fekade Demeke Bayou; Mastewal Arefaynie (Cost Effectiveness and Resource Allocation, 2024)
Abstract Background Ethiopia, like many low-income countries, faces significant challenges in providing accessible and affordable healthcare to its population. Health expenditure is a critical factor in determining the quality and accessibility of healthcare. However, high health expenditure can also have detrimental effects on households, potentially leading to impoverishment. To the best knowledge of investigators, no similar study has been conducted in Ethiopia. Therefore, this systematic review and meta-analysis aimed to determine the pooled burden of health expenditure on household impoverishment in Ethiopia. Methods This systematic review and meta-analysis used the updated Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guideline. PubMed, Cochrane Library, HINARI, Google Scholar and Epistemonikos electronic databases were searched systematically. Moreover, direct manual searching through google was conducted. The analysis was performed using STATA version 17 software. Heterogeneity and publication bias were assessed using I2 statistics and Egger’s test, respectively. The trim and fill method was also performed to adjust the pooled estimate. Forest plots were used to present the pooled incidence with a 95% confidence interval of meta-analysis using the random effect model. Results This systematic review and meta-analysis included a total of 12 studies with a sample size of 66344 participants. The pooled incidence of impoverishment, among households, attributed to health expenditure in Ethiopia was 5.20% (95% CI: 4.30%, 6.20%). Moreover, there was significant heterogeneity between the studies (I2 = 98.25%, P = 0.000). As a result, a random effect model was employed. Conclusion The pooled incidence of impoverishment of households attributed to their health expenditure in Ethiopia was higher than the incidence of impoverishment reported by the world health organization in 2023.